Evaluation of total sialic acid, paraoxonase activity, and malondialdehyde in cows with subclinical paratuberculosis - Akyuz, E; Kükürt, A; Makav, M; Gökçe, E; Eroğlu, HA; Deveci, HA; Gökce, G; Karapehlivan, M (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, it was aimed to evaluate total sialic acid (TSA), paraoxonase activity (PON1), malondialdehyde (MDA) and some serum biochemical parameters in cows with subclinical paratuberculosis. Paratuberculosis (PT) test was performed on 500 cows aged 2-6 years by ELISA method. Twenty-four cows diagnosed with paratuberculosis constituted the PT group and 12 healthy cows constituted the control group. According to the results, alanine aminotransferase (ALT), aspartate aminotransferase (AST) and UREA levels were found to be statistically higher (p <0.05) in the group with paratuberculosis compared to the control group. Iron (Fe) levels were found to be lower than the control group (p> 0.05). Compared to the control group, there was a decrease in PON1 activity and a significant increase in TSA and MDA levels in the PT group (p <0.05). In conclusion, in subclinical paratuberculosis infection, the long incubation period and the absence of clinical findings until advanced stages constitute a handicap. However, our findings show that the determination of lipid peroxidation (MDA), PON1 activity and TSA concentration caused by the inflammatory and oxidative stress state caused by the infection can be used as new biomarkers for this infection.